2021
DOI: 10.1101/2021.05.11.443597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Drosophila orthologue of the primary ciliary dyskinesia-associated gene, DNAAF3, is required for axonemal dynein assembly

Abstract: Ciliary motility is powered by a suite of highly conserved axoneme-specific dynein motor complexes. In humans the impairment of these motors through mutation results in the disease, Primary Ciliary Dyskinesia (PCD). Studies in Drosophila have helped to validate several PCD genes whose products are required for cytoplasmic pre-assembly of axonemal dynein motors. Here we report the characterisation of the Drosophila homologue of the less known assembly factor, DNAAF3. This gene, CG17669 (Dnaaf3), is expressed ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…We first analysed flies with a CRISPR-engineered null mutation of Dnaaf3 (CG17669), the orthologue of the human dynein assembly factor and PCD gene, DNAAF3. Human DNAAF3 is required for all dynein assembly, and Drosophila Dnaaf3 CR mutant flies show absence of dynein arms from the chordotonal neuron cilia (zur Lage et al, 2021). However, we found that Iav localisation was unaltered in Dnaaf3 CR mutant antennae (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We first analysed flies with a CRISPR-engineered null mutation of Dnaaf3 (CG17669), the orthologue of the human dynein assembly factor and PCD gene, DNAAF3. Human DNAAF3 is required for all dynein assembly, and Drosophila Dnaaf3 CR mutant flies show absence of dynein arms from the chordotonal neuron cilia (zur Lage et al, 2021). However, we found that Iav localisation was unaltered in Dnaaf3 CR mutant antennae (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They were mounted in a 2.5% n-Propyl gallate/glycerol mix. The following primary antibodies were used: Goat anti-GFP (1:500: Abcam, ab6673), Rabbit anti-mCherry (1:500; Abcam, ab167453), Mouse anti-NompC (1:250; Liang et al 2011), Rabbit anti-Sas4 (1: 350; gift from Jordan Raff), Rabbit anti-Dnah5 (1:2000; (zur Lage et al, 2021). The secondary antibodies (Life Technologies) were all used at a 1:500 concentration and included: Donkey anti goat (Alexa Fluor® 488, A11055), Donkey anti mouse (Alexa Fluor® 568, A10037), Donkey anti rabbit (Alexa Fluor® 647, A31573).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations